Transcriptional upregulation of p19INK4d upon diverse genotoxic stress is critical for optimal DNA damage response - Ceruti, Julieta María (2008)
p19INK4d promotes survival of several cell lines after UV irradiation due to enhanced DNA repair, independently of CDK4 inhibition. To further understand the action of p19INK4d in the cellular response to DNA damage, we aimed to elucidate whether this novel regulator plays a role only in mechanisms triggered by UV or participates in diverse mechanisms initiated by different genotoxics. We found that p19INK4d is induced in cells injured with cisplatin or beta-amyloid peptide as robustly as with UV. The mentioned genotoxics transcriptionally activate p19INK4d expression as demonstrated by run-on assay without influencing its mRNA stability and with partial requirement of protein synthesis. It is not currently known whether DNA damage-inducible genes are turned on by the DNA damage itself or by the consequences of that damage. Experiments carried out in cells transfected with distinct damaged DNA structures revealed that the damage itself is not responsible for the observed up-regulation. It is also not known whether the increased expression of DNA-damage-inducible genes is related to immediate protective responses such as DNA repair or to more delayed responses such as cell cycle arrest or apoptosis. We found that ectopic expression of p19INK4d improves DNA repair ability and protects neuroblastoma cells from apoptosis caused by cisplatin or beta-amyloid peptide. Using clonal cell lines where p19INK4d levels can be modified at will, we show that p19INK4d expression correlates with increased survival and clonogenicity. The results presented here, prompted us to suggest that p19INK4d displays an important role in an early stage of cellular DNA damage response